Avaliação do biosilicato® e do flúor gel acidulado na permeabilidade da dentina radicular. Estudo in vitro - Pinheiro, Michele Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Biomaterials, such as bioactive glasses and glass ceramics have been proposed for the treatment of cervical dentinal hypersensitivity (HSDC) by forming a hydroxycarbonate apatite layer obliterating the dentinal tubules. The aim of the study was to evaluate in vitro the effectiveness of a new bioactive glass ceramic particulate called Biosilicate®, added to the acidulated fluoride gel and acidulated fluoride gel itself to reduce or eliminate dentinal permeability before and after dietary acid challenges. Two hundred and forty freshly extracted third molars had the crown sectioned above at the cemento enamel junction, the pulp tissue removed and the cervical root dentin exposed using a cylindrical high-speed bur (about 1 mm in depth substance loss). From each root fragment, one specimen was prepared, totaling 240 specimens randomized into 2 groups differed on the product used (Biosilicate® more fluoride gel or fluoride gel) and 10 subgroups, which differed as to the substance used for the challenges acids (lemon, orange, pineapple, cherry, grape, vinegar, white wine, coca cola, lemon-flavored Gatorade, orange juice industrialized).The specimens were attached to a hydraulic pressure apparatus to evaluate the alterations of root dentin permeability after treatment with Biosilicate® and Fluoride gel and after acid challenges. The dentin permeability was measured after the following sequential steps: (1) after etching of the specimens obtained a value of maximum permeability of each specimen, (2) after treatment with Biosilicate® and Fluorine or Fluorine, (3) after dietary acid challenges; this last stage being repeated 2 more times. All data were converted to percentage values being considered the first step to 100%.After statistical analysis using the Mann-Whitney, Kruskal-Wallis and Wilcoxon was determined that both products decreased statistically dentin permeability however (Complete abstract electronic access below).

Biomateriais, tais como vidros bioativos e vidros cerâmicos, têm sido propostos para o tratamento da Hipersensibilidade Dentinária Cervical (HSDC) por formarem sobre a dentina uma camada de hidroxicarbonatoapatita obliterando os túbulos dentinários.O objetivo desse estudo foi avaliar in vitro a efetividade de uma nova vitrocerâmica bioativa particulada denominada Biosilicato®, adicionada ao flúor gel acidulado, e do próprio flúor gel acidulado em reduzir ou eliminar a permeabilidade dentinária antes e após desafios ácidos da dieta. Foram utilizados duzentos e quarenta terceiros molares recém-extraídos que tiveram a coroa seccionada ao nível da junção cemento-esmalte, o tecido pulpar removido e a dentina radicular cervical exposta utilizando uma fresa cilíndrica de alta rotação (aproximadamente 1 mm de profundidade). De cada raiz um espécime foi preparado, totalizando 240 espécimes distribuídos randomicamente em 2 grupos que diferiram quanto ao produto utilizado (Biosilicato® mais flúor gel ou Flúor gel) e 10 subgrupos, que diferiram quanto às substancia utilizadas para os desafios ácidos (limão, laranja, abacaxi, acerola, uva, vinagre, vinho branco, coca cola, Gatorade sabor limão, suco de laranja industrializado). Os espécimes foram fixados a um aparelho de pressão hidráulica para avaliar as alterações na permeabilidade da dentina após o tratamento com o Biosilicato® mais flúor gel ou com flúor gel e após desafios ácidos. A permeabilidade dentinária foi medida após as seguintes etapas sequenciais: (1) após condicionamento ácido dos espécimes obtendo um valor de permeabilidade máxima de cada espécime; (2) após tratamento com Biosilicato® mais Flúor gel ou Flúor gel; (3) após desafios ácidos da dieta; sendo essa última fase repetida mais 2 vezes. Todos os dados foram convertidos em valores de porcentagem sendo considerada a primeira medida (Resumo completo, clicar acesso eletrônico abaixo).
Keywords: Dentina - Sensibilidade; Camada de esfregaço; Flúor; Materiais biomédicos; Sensitivity of dentin